Study of Interior Materials as Passive Fire Protection in Karaoke Building (Case Study: Masterpiece Signature Family KTV Medan) (International Journal of Architecture and Urbanism, 2020)
The fire incident in karaoke buildings in Indonesia which claimed many lives has occurred several times. According to the National Academy of Science US, the smoke toxins that come out of the fire disaster cause 50-80% of deaths. Refers to the data, it is necessary to check further about the building material response to fire during a fire incident. Masterpiece Signature Karaoke is a karaoke building that classified as large and magnificent in the city of Medan which has various material so that it is necessary to study the interior material as passive fire protection. The purpose is to find out how to assess the reliability of fire passive protection regard to the interior materials and recommendations or descriptions of right interior material planning using the Analytical Hierarchy Process (AHP). This method is efficacious to solve the problem of reliability in using interior materials as passive fire protection in Masterpiece Signature Family KTV Medan building with the results of an Adequate Level of reliability. Then, design recommendations were given for the use of interior materials in karaoke building to improve the reliability results to be better.The results are useful as information for other researchers and karaoke buildings regarding passive fire protection systems at the Masterpiece Signature Family KTV Medan.